Het landschap in het Brusselse overheidsoptreden: een categorie in ontwikkeling - Sophie Hubaut (Brussels Studies, 2021)
As the number of references to landscape increases in the Brussels-Capital Region, the article analyses its place and meaning within the Regional Development Plans (1995-2018). The article intends to show that landscape may be considered as a category of Brussels public action and that in this sense it constitutes a good indicator of its evolution. The analysis allows us to identify significant changes, such as the progressive association of landscape with nature as the sustainability framework replaced the interest in heritage, and its change of scale in connection with the process of metropolisation. It also highlights certain contents which are more stable over time, such as the association of landscape with the imaginary of slow mobility or the view of it as a relatively positive and consensual subject.